Cryoballoon ablation in the elderly: one year outcome and safety of the second-generation 28mm cryoballoon in patients over 75 years old. Issue 5 (27th June 2017) - Tscholl, Verena; Lin, Tina; Lsharaf, Abdullah Khaled-A; Bellmann, Barbara; Nagel, Patrick; Lenz, Klaus; Landmesser, Ulf; Roser, Mattias; Rillig, Andreas
Abstract: Aims: The efficacy of the second-generation cryoballoon (CB) ablation in patients with atrial fibrillation (AF) has been demonstrated previously. Data on the efficacy of CB ablation in elderly patients is missing. The aim of this study was to evaluate the long-term success rate of pulmonary vein isolation (PVI) in patients ≥75 years vs. <75 years using the second-generation 28mm CB. Methods and results: Eighty patients [ n  = 40 ≥75 years (Group 1); n  = 40 <75 years (Group 2)] with paroxysmal [ n  = 37 (46%) or persistent ( n  = 43 (54%)] AF were included. Median follow-up was 12 [6;18] months (Group 1 vs. 13 [6;27]) months (Group 2; P  = 0.8). PVI was performed in all patients using cryoablation. Follow-up was obtained using 24h-Holter monitoring or via an implanted loop recorder or pacemaker. CHA2 DS2 VASc-Score (Group 1: 4 [4;5] vs. Group 2: 2 [1;3], P  < 0.001) and HASBLED-Score (Group 1: 2 [2;3] and Group 2: 2 [1;3], ( P  = 0.009)) differed significantly between the two groups. Mean fluoroscopy time was 22.9 [16.3;31.9] in Group 1 and 24.5 [19.1;30.6] in Group 2 ( P  = 0.75), and mean procedure time was 125 min [105;151] in Group 1 and 130.5 min [117.5;147.3] in Group 2 ( P  = 0.66). Arrhythmia recurrence was similar in Group 1 and Group 2 (12/40 (30%) vs. 10/40 (25%) ( P  = 0.62). One transient ischaemic attack occurred in Group 2. No further major complications were documented in this patients cohort. Conclusion: CB ablation in patients ≥75 years has favourable success rates and similar complication rates compared with patients <75 years.